60 minutes. Eyewitness. Part one - Finkelstein, Shari; Stahl, Lesley; CBS News (New York, NY : Columbia Broadcasting System, 2009)
So how accurate is eyewitness testimony? As Lesley Stahl found out firsthand, memory is malleable and can easily be influenced and corrupted. This is part one of a two-part segment.
Title from resource description page (viewed October 23, 2015).
In English.
Keywords: DNA fingerprinting; Eyewitness identification; Recognition (Psychology); Recollection (Psychology); DNA Fingerprinting; Mental Recall; Empreintes génétiques.; Identification par témoin oculaire; Reconnaissance (Psychologie); Rappel (Psychologie); DNA fingerprinting; Eyewitness identification; Recognition (Psychology); Recollection (Psychology); Online media; Television news programs; Television news programs; Téléjournaux.